The effect of motor vehicle emission towards lead (Pb) content of rice field soil with different clay content - C C Wati; S Prijono; Z Kusuma (Journal of Degraded and Mining Lands Management, 2015)
Motor vehicle gas emission contains lead (Pb) which is a hazardous and toxic substance. Agricultural land, especially rice field, which is located nearby roads passed by many motor vehicle, are susceptible to the accumulation of Pb. If Pb is permeated by plants cultivated in the rice field, it will be very hazardous for humans as they are the final consumers. Hence, it is essential to identify Pb content of rice-field soil initiated by motor vehicle gas emission. This study was aimed to identify the effects of motor vehicle density, the distance between rice-field and road, and the clay content of soil towards Pb content of soils in Blitar and Ngawi Regencies of East Java. The method used for the study was survey method managed by using three-factor nested design with three replicates. The results of this study showed that motor vehicle density and the distance of rice field to road provide significant affected the total of Pb content of soil. However, the dissemination pattern of Pb in the soil was irregular due to the factors of climate and environment. Before Pb reached soil surface, Pb was spread out in the air due to the effect of temperature, wind velocity, vehicle velocity, size of vehicle, and road density. Consequently, the location with low motor vehicle density and positioned faraway to the road had higher total rate of Pb than the location with high motor vehicle density and positioned nearby the road. Clay content affected the total rate of Pb content as much as 37%, every 1% increase of clay content increased the total rate of Pb as much as 0.08 mg/kg.